Distortion of the Ontological Construction of Gender in Kapur’s Custody (Texas Journal of Multidisciplinary Studies, 2022)
The paper aims to uproot the male-oriented Indian social culture of colonizing women with a vision of distorting the ontological construction of gender identity and battling against the androcentric culture of India by two major female characters of Manju Kapur’s novel, Custody (2011), Shagun and Ishita. Shagun and Ishita not only get divorced but also remarry other men to signify how modern women are capable of challenging the patriarchal Indian culture for their liberation and identity. To survey the aftermath consequences of suppression on women, divorce, and remarriage, feminist theory, with special focus on the theorization of French feminists such as Simon de Beauvoir, Christine Delphy, Sheila Ruth, is used as a research tool. And the qualitative, analytical, explorative research method is used to test the hypothesized issues. The major finding of the research paper is that though Kapur is successful to resist the patriarchal society that attempts to subjugate women, patriarchal domination is still stimulating modern society and women are facing problems due to uncertainties of matrimony, infertility. It is expected that researchers intending to probe into the creative world of Kapur with a feminist approach can obtain this work as a reference.